2004
DOI: 10.5194/acp-4-169-2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NO<sub>3</sub> radicals in oxidation processes in the eastern Mediterranean troposphere during the MINOS campaign

Abstract: Abstract. During the MINOS campaign (28 July-18 August 2001) the nitrate (NO 3 ) radical was measured at Finokalia station, on the north coast of Crete in South-East Europe using a long path (10.4 km) Differential Optical Absorption Spectroscopy instrument (DOAS). Hydroxyl (OH) radical was also measured by a Chemical Ionization MassSpectrometer . These datasets represent the first simultaneous measurements of OH and NO 3 radicals in the area. NO 3 radical concentrations ranged from less than 3×10 7 up to 9×10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 33 publications
10
94
0
2
Order By: Relevance
“…55,56 This result may well support our speculation that on the atmospheric particles, N 2 O 5 would ionize in the adsorbed water, leading to a sink of NO 3 and the generation of NO 2 + . As a result, the low ratio of [NO 3 (g)]/ [NO 2 + (aq)] on the particle surface would make the heterogeneous reaction of PAHs significantly different from that in the gas phase, causing different nitro-PAHs isomers to be produced.…”
Section: ■ Atmospheric Implicationssupporting
confidence: 82%
“…55,56 This result may well support our speculation that on the atmospheric particles, N 2 O 5 would ionize in the adsorbed water, leading to a sink of NO 3 and the generation of NO 2 + . As a result, the low ratio of [NO 3 (g)]/ [NO 2 + (aq)] on the particle surface would make the heterogeneous reaction of PAHs significantly different from that in the gas phase, causing different nitro-PAHs isomers to be produced.…”
Section: ■ Atmospheric Implicationssupporting
confidence: 82%
“…Hua dust samples mainly originated from Gobi plants. NO (Formenti et al, 2011;Jöckel et al, 2003;Seinfeld and Pandis, 1998), but the NO − 3 formation is about 10 times faster than that of SO 2− 4 (Rodhe et al, 1981;Vrekoussis et al, 2004Vrekoussis et al, , 2007. Field observation showed that ground surface levels of NO 2 and SO 2 are similar in inland China.…”
Section: Difference In Chemical Composition Between Xi'an and Mt Huamentioning
confidence: 88%
“…Higher relative humidity during dew nights relative to nondew nights (Fig. 1) is likely to have a limiting influence on oxidation of GEM by NO 3 due to enhanced depletion of the radical (Geyer et al, 2001;Vrekoussis et al, 2004);Peleg et al (2015) noted a significant anti-correlation between relative humidity and NO 3 , as well as between relative humidity and GOM. They also highlighted possible evidence of GEM oxidation by O 3 , albeit only at levels above 47 ppb, higher than the nocturnal concentrations observed here.…”
Section: Nocturnal Atmospheric Mercury Depletion Eventsmentioning
confidence: 99%